Risk and Protective Factors of Generalized Anxiety Disorder of Elite Collegiate Athletes: A Cross-Sectional Study - Chunxiao Li; Rong Fan; Rong Fan; Jian Sun; Guoxing Li (Frontiers Media S.A., 2021)
The aim of this study was to examine the prevalence of Generalized Anxiety Disorder (GAD) and its risk and protective factors in elite collegiate athletes. A cross-sectional survey was conducted during the 2019 in-season. A sample of elite collegiate athletes (n = 285) from China completed a self-report form assessing GAD and potential predictors including age, gender, sport type, sport achievement, sport injury, attention deficit hyperactivity disorder (ADHD), fear of failure, mental toughness, and satisfaction in sport. The overall prevalence of GAD symptoms was 22%. The results of zero-order correlation showed that age, gender, sport type, and sport achievement were not significantly related to GAD. However, athletes with a history of sport injury, a high risk of ADHD, and a high level of fear of failure had a significant and positive association with GAD (r = 0.14-0.54). Meanwhile, high levels of mental toughness and satisfaction in sport were significantly and negatively related to GAD (r = −0.22 to −0.24). The results of multiple regression analysis indicated that sport injury, ADHD, and fear of failure were significant risk factors of GAD (β = 0.10-0.40). These findings suggest the necessity to understand the GAD symptoms in elite collegiate athletes. Further research is needed to better understand and support the mental health of this target group.